PELATIHAN FOTO PRODUK KREATIF UNTUK MENINGKATKAN PROMOSI DIGITAL USAHA MIKRO DAN KECIL (UMK) DI KABUPATEN BEKASI - Permatasari, Anggraeni; Witono, A.B.M.; Retnowati, Retnowati (Jurnal Abdi Insani, 2024)
Changes in consumer behavior in the digital era require Micro and Small Enterprises (MSMEs) to adapt and change various aspects of their business. One of them is digital marketing. An effective marketing strategy today is through social media. MSMEs must display attractive and informative business or product advertisements to attract consumers online. Therefore, the Business Administration Study Program at President University needs training to improve photography skills so that MSMEs can promote products through websites, e-commerce, social media, and other digital platforms. This activity collaborates with the West Java Province Cooperatives, Micro, Small, and Medium Enterprises Service (DINKOP-UMKM). The activity was held on July 22, 2024, at the Computer Lab, President University, Cikarang-Jababeka, Bekasi Regency. This training lasted one full day, with fun classes and adequate facilities. The material provided consists of photography theory and practice, such as photography knowledge, lighting techniques, color theory, and design techniques to enhance the product's appearance. Based on the evaluation results through the questionnaire, it can be concluded that the creative product photography training that was carried out was easy to follow, and participants gained more confidence to photograph and design product advertisements independently. Participants also learned the entire creative process behind product photography, choosing properties, and how to arrange products to get attractive images. At the end of the activity, participants took home the product photography results to be used directly for online business promotions on social media, websites, or other digital platforms.